2017
DOI: 10.18632/oncotarget.23483
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1/miR-101-3p/MCL1 axis mediates cisplatin resistance in lung cancer

Abstract: In this study, we investigated the mechanism by which lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) mediates cisplatin resistance in lung cancer. Lung cancer patients with high MALAT1 levels were associated with cisplatin resistance and low overall survival. Moreover, cisplatin-resistant A549/DDP cells showed higher MALAT1 expression than cisplatin-sensitive lung cancer cells (A549, H460, H1299 and SPC-A1). Dual luciferase reporter and RNA immunoprecipitation assays showed direct bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Therefore, the aim of our study was to explore the functional mechanism of LINC00461 in lung adenocarcinoma in relation to HOXA10.Subsequently, the key findings obtained from this study provided evidence that LINC00461 silencing could potentially suppress lung adenocarcinoma cell migration, invasion while enhancing radiosensitivity via downregulation of HOXA10 by binding to miR-195.Initially, our findings demonstrated that LINC00461 was up-regulated in lung adenocarcinoma and the ectopic expression of LINC00461 stimulated lung adenocarcinoma cell proliferation, migration and invasion but inhibited radiosensitivity. LncRNA can potentially affect gene expression by regulating chromatin modifications, transcription and post-transcriptional mechanisms and can therefore regulate cell apoptosis, proliferation, metastasis and chemo-resistance 21. LncRNAs have been reported to be involved in the pathology of lung cancer 22.…”
mentioning
confidence: 99%
“…Therefore, the aim of our study was to explore the functional mechanism of LINC00461 in lung adenocarcinoma in relation to HOXA10.Subsequently, the key findings obtained from this study provided evidence that LINC00461 silencing could potentially suppress lung adenocarcinoma cell migration, invasion while enhancing radiosensitivity via downregulation of HOXA10 by binding to miR-195.Initially, our findings demonstrated that LINC00461 was up-regulated in lung adenocarcinoma and the ectopic expression of LINC00461 stimulated lung adenocarcinoma cell proliferation, migration and invasion but inhibited radiosensitivity. LncRNA can potentially affect gene expression by regulating chromatin modifications, transcription and post-transcriptional mechanisms and can therefore regulate cell apoptosis, proliferation, metastasis and chemo-resistance 21. LncRNAs have been reported to be involved in the pathology of lung cancer 22.…”
mentioning
confidence: 99%
“…miR-101-3p is a member of the miR-101 family, and a recent study indicated that it has tumor suppressor effects in patients with NSCLC ( 16 ). However, to the best of our knowledge, a limited number of studies have addressed the association between miR-101-3p and adjuvant chemotherapy in patients with NSCLC ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…By combining novel MCL1 inhibitors with low dose cisplatin, we could potentially combat cisplatin resistance and/or decrease the therapeutic dosing. This rationale is supported by recent accounts that knockdown of MCL1 sensitizes cancer cells to cisplatin-induced apoptosis 65,66 .…”
Section: Discussionmentioning
confidence: 71%